The Effect of Overtime and Workload towards Employee Productivity With Burnout as Mediating Variable: (A Research at PT. RAPP) - Iis Farida Okta; M. Alkadri Perdana (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research aims to determine the influence and how much influence overtime and workload on employee productivity with burnout as mediating variable at PT. RAPP. Utilizing a quantitative method, non-probability sampling with purposive sampling, data collection technique using questionnaire with sample of 80 employees. Data analysis used was descriptive analysis, classical assumptions, Multiple Regression Analysis, R2 Test, F Test, T Test, and mediation test. The results of this research indicate that: (1) Overtime significantly and negatively influence employee productivity with tcount -2.830 < ttable 1.99167 and Sig. 0.006 < 0.05 (2) Workload significantly and positively influence employee productivity with tcount 11.906 > ttable 1.99167 and Sig 0.000 < 0.05 (3) Overtime significantly and negatively influence burnout with tcount -6.117 < ttable 1.99125 and Sig 0.001 < 0.05 (4) Workload significantly and positively influence burnout with tcount 3.821 < ttable 1.99125 and Sig 0.001 < 0.05 (5) Burnout significantly and negatively influence employee productivity with tcount -6.450 < ttable 1.99167 and Sig. 0.000 < 0.05 (6) There is mediating role burnout on the influence of overtime on employee productivity with Z-Score 4.43 > 1.96 (7) Burnout does not mediate the influence of workload on employee productivity with Z-Score -3.28 < 1.96.